Outcome of pN0 Triple‐Negative Breast Cancer with or without Lymph Node Irradiation: A Single Institution Experience. Issue 5 (4th June 2016) - Khalifa, Jonathan; Duprez‐Paumier, Raphaelle; Filleron, Thomas; Lacroix Triki, Magali; Jouve, Eva; Dalenc, Florence; Massabeau, Carole
Abstract: The optimal management of patients with pathologically node‐negative triple‐negative breast cancer (pN0 TNBC) remains unclear. We hypothesized that lymph node irradiation (LNI; internal mammary chain/periclavicular irradiation) had an impact on outcomes of pN0 TNBC. A cohort of 126 consecutive patients with pN0 TNBC treated between 2007 and 2010 at a single institute were included. All radiotherapy (breast/chest wall, ±LNI) was delivered adjuvantly, following completion of surgery ± chemotherapy. Tumors were reviewed and histologic features were described. Tissue microarrays were constructed and tumors were assessed by immunohistochemistry using antibodies against ER, PR, HER2, Ki‐67, cytokeratins 5/6, 14, epidermal growth factor receptor and androgen receptor. Patients were divided into two groups for statistical analysis: LNI (LNI+) or no LNI (LNI−). We focused on disease‐free survival (DFS), metastasis‐free survival (MFS), and overall survival (OS). Fifty‐seven and 69 patients received or not LNI, respectively. Median age was 52 (range [25–76]) and 55 (range [29–79]) in LNI+ and LNI− group (p = 0.23). LNI was associated with larger tumors (p = 0.033), central/internal tumors (33 versus 4, p < 0.01) and more chemotherapy (86% versus 59.4% p < 0.01). The median follow‐up was 53.5 months. The rate of first regional relapse (associated or not with distant relapse) was low in both groups. There was no difference in 4‐year DFS (82.2% versus 89.9%; p = 0.266), MFS (87.0% versus 91.1%; p = 0.286) and OS (85.8% versus 89.9%; p = 0.322) between LNI+ and LNI− group, respectively. In univariate analysis, only clinical size (T >10 mm versus ≤10 mm), histologic size (pT >10 mm versus ≤10 mm) and grade 3 (versus grade 2) were found to be significantly associated with shorter DFS. Omission of LNI in patients with pN0 TNBC does not seem to result in poorer outcome. Further studies are needed to specifically evaluate LNI in pN0 TNBC with histologic grade 3 and/or (p)T >10 mm.